Takane & Hana. 8 - Shiwasu, Yuki; MacFarlane, Ysabet Reinhardt (Shojo beat manga., 2019)
"A strong-willed high school girl and a hot, young scion of a business empire can't help wanting to outwit each other every chance they get ... But could these opposites be conning themselves out of the perfect match?! ... Valentine's day rolls around, and Hana wonders what she should give Takane even as she struggles to hide her feelings from him. Meanwhile, Hana's father poses a question to Takane--exactly how long is he planning to continue his arranged marriage relationships with Hana?"--Provided by publisher.